Patient preferences for the treatment of systemic sclerosis-associated interstitial lung disease: a discrete choice experiment - Bruni, Cosimo; Heidenreich, Sebastian; Duenas, Ashley; Hoffmann-Vold, Anna-Maria; Gabrielli, Armando; Allanore, Yannick; Chatelus, Emmanuel; Distler, Jörg; Hachulla, Eric; Hsu, Vivien M.; Hunzelmann, Nicolas; Khanna, Dinesh; et al. (Rheumatology, 2022)
Objectives Treatments for SSc-associated interstitial lung disease (SSc-ILD) differ in attributes, i.e. mode of administration, adverse events (AEs) and efficacy. As physicians and patients may perceive treatments differently, shared decision-making can be essential for optimal treatment provision. We therefore aimed to quantify patient preferences for different treatment attributes. Methods Seven SSc-ILD attributes were identified from mixed-methods research and clinician input: mode of administration, shortness of breath, skin tightness, cough, tiredness, risk of gastrointestinal AEs (GI-AEs) and risk of serious and non-serious infections. Patients with SSc-ILD completed an online discrete choice experiment (DCE) in which they were asked to repeatedly choose between two alternatives characterized by varying severity levels of the included attributes. The data were analysed using a multinomial logit model; relative attribute importance and maximum acceptable risk measures were calculated. Results Overall, 231 patients with SSc-ILD completed the DCE. Patients preferred twice-daily oral treatments and 6-12 monthly infusions. Patients' choices were mostly influenced by the risk of GI-AEs or infections. Improvement was more important in respiratory symptoms than in skin tightness. Concerning trade-offs, patients accepted different levels of increase in GI-AE risk: +21% if it reduced the infusions' frequency; +15% if changing to an oral treatment; up to +37% if it improved breathlessness; and up to +36% if it reduced the risk of infections. Conclusions This is the first study to quantitatively elicit patients' preferences for treatment attributes in SSc-ILD. Patients showed willingness to make trade-offs, providing a firm basis for shared decision-making in clinical practice.
CRIS-Team WoS Importer:2022-04-08